The oxygen isotopic composition (18O/16O) in the dust of comet 67P/Churyumov-Gerasimenko measured by COSIMA on-board Rosetta - J A Paquette; C Engrand; M Hilchenbach; N Fray; O J Stenzel; J Silen; J Rynö; J Kissel; Cosima Team (United Kingdom, 2022)
The oxygen isotopic ratio 18O/16O has been measured in cometary gas for a wide variety of comets, but the only measurements in cometary dust were performed by the Stardust cometary sample return mission. Most such measurements find a value of the ratio that is consistent with Vienna Standard Mean Ocean Water (VSMOW) within errors. In this work we present the result of a measurement, using the COSIMA (the COmetary Secondary Ion Mass Analyser) instrument on the Rosetta orbiter, of the oxygen isotopic ratio in dust from Comet 67P/Churyumov-Gerasimenko. Measuring the 18O/16O ratio with COSIMA is challenging for a number of reasons, but it is possible with a reasonable degree of precision. We find a result of 2.00 × 10−3 ± 1.2 × 10−4, which is consistent within errors with VSMOW.